The last of academic writing: academic community, performance and material environment - Petr A. Safronov (Высшее образование в России)
Starting from his administrative background as a chair of the faculty the author discussesadvantages and shortcomings of the academic writing courses in Russian universities. After that he goes further to convey the idea of substantial shift in the understanding of science happening nowadays. Based on the performative qualities of the research this shift undermines the role of writing as a core part of the whole scientific enterprise. Project work and planning are taking the leading role both in research practice and teaching.